Measurement of tensor analyzing powers in deuteron photodisintegration; Spin 2004 - Toporkov D. K.; Arenhove I. H.; Barkov L. M.; Belostotsky S. L.; Dmitriev V. F>; Dyug M. V.; Gilman R.; Grigoriev A. V.; Holt R. J.; de Jager C. W.; Lazarenko B. A.; Loginov A. Yu.; et al. (2004, 2004)
В фонде НТБ ТПУ отсутствует